The relational database dictionary : a comprehensive glossary of relational terms and concepts, with illustrative examples - Date, C. J. (O'Reilly, 2006)
"Avoid misunderstandings that can affect the design, programming, and use of database systems. Whether you're using Oracle, DB2, SQL Server, MySQL, or PostgreSQL, The Relational Database Dictionary will prevent confusion about the precise meaning of database-related terms helping to ensure the success of your database projects. Carefully reviewed for clarity, accuracy, and completeness, this authoritative and comprehensive quick reference contains more than 600 terms, many with examples, covering issues and concepts arising from the relational model of data. This one-of-a-kind dictionary provides a single, compact source where DBAs, database designers, DBMS implementers, application developers, and database professors and students can find the accurate definitions they need on a daily basis - information that isn't readily available anywhere else. If you're working with or learning about relational databases, you need this pocket-size quick reference."--Jacket